O livro didático de português: abordagem discursiva de exercícios de compreensão de texto - Carvalhaes, Wesley Luis (2016)
The doctoral dissertation O livro didático de português: abordagem discursiva de exercícios de compreensão de texto (The Portuguese textbook: a discourse approach to text comprehension exercises) aims to analyze, under the lights of theoretical contributions from text and discourse studies, the operations proposed by text comprehension questions in the Portuguese textbook (Livro Didático de Português, or LDP), investigating in what manner these questions bring to life the conceptions of language, teaching and reading presented by the authors in the teacher’s book that comes along with the LDP. The research takes as its analytical corpus the text interpretation questions from two high school ninth grade LDPs. Both books were amongst the most adopted in state public schools of the city of Goiânia (Goiás State, Brazil), under the sponsorship of the textbook national program (Plano Nacional do Livro Didático, or PNLD) for the triennium 2011-2013. They are: Cereja and Magalhães (2010), and Beltrão and Gordilho (2010). The study adopts the concept of language as verbal interaction (BAKHTIN; VOLOCHÍNOV, 2006), and perceives the text as a social and historical process, characterized by the dialogism. Reading is faced as a social activity, through which the meaning is built in the course of social interaction situations. The investigation seizes its north from the notion of discourse as a meaning effect (PÊCHEUX, 1990, 1997), and treats reading in this perspective, since what someone enunciates is connected to the social and historical moment in which he or she is inserted, as well as to other factors that influence the speech and the meanings that can be built from it. In order to observe the historical conditions for producing and distributing didactic materials in Brazil, this study takes a historiographical and linguistic path of the LDP, showing that the government controls the didactic production through mechanisms such as the above-mentioned PNLD. Regarding the text comprehension questions, the documental research methodology has been applied to the study, with a qualitative approach. The analytical categories chosen are the typologies of Marcuschi (1996). The analysis shows that the two LDPs’ teacher’s books in perspective present, as theoretical support for their elaboration, notions of language, text, and reading, rooted on Bakhtin’s concept of language as verbal interaction. However, these notions do not come to reality in the majority of the exercises proposed for working with the texts. As for the LDPs’ text comprehension questions analyzed, they are centered mainly on elements objectively found in the text or on operations of metalinguistic nature. Therefore, they do not take into consideration the extra-textual elements to be discussed in activities that comprehend reading as a social practice. In this sense, there is a mismatch between the theoretical aspects indicated in the LDPs’ teacher’s books analyzed and the proposed questions for approaching the text. Consequently, the LDPs’ text interpretation exercises analyzed do not materialize the language, teaching, reading, and meaning notions displayed in the corresponding teacher’s textbook.